Juegos digitales para el aprendizaje de las matemáticas en educación básica - Daquilema Gavilanes, Mariana Elizabeth (2024)
The present research aims to propose the incorporation of digital games for mathematics learning in the seventh year of basic general education. The problem identified was the poor performance and disinterest of students in mathematics, exacerbated by traditional teaching methods that did not capture their interest or adapt to their individual needs. The methodology of this research includes a meticulous bibliographic review of digital games in mathematics, describing their characteristics, benefits, and challenges in the educational context. In addition, a comparative analysis of available educational tools was designed, assessing criteria such as alignment with the national curriculum, ability to foster critical thinking, ease of use, and effectiveness in improving understanding of mathematical concepts. The resulting proposal incorporates four digital games using the Educaplay and Wordwall platforms, covering topics such as fractions and decimals, linear equations, geometry and data, and probability analysis. Each theme is developed over a week with two-hour daily activities. Teachers prepare and configure the interactive tools and monitor the progress of the students, while they actively participate in the activities and challenges designed, receiving immediate feedback that facilitates their understanding and retention of concepts. In conclusion, the implementation of this proposal not only improves the academic performance of students in mathematics but also fosters a more dynamic and motivating learning environment, offering an innovative solution to today’s educational challenges.